2017
DOI: 10.1007/s13201-017-0612-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of land-use on groundwater quality: GIS-based study from an alluvial aquifer in the western Ganges basin

Abstract: In this study, groundwater quality of an alluvial aquifer in the western Ganges basin is assessed using a GIS-based groundwater quality index (GQI) concept that uses groundwater quality data from field survey and laboratory analysis. Groundwater samples were collected from 42 wells during pre-monsoon and post-monsoon periods of 2012 and analysed for pH, EC, TDS, Anions (Cl, SO 4 , NO 3 ), and Cations (Ca, Mg, Na). To generate the index, several parameters were selected based on WHO recommendations. The spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 17 publications
4
9
0
1
Order By: Relevance
“…These results are consistent with the results of other studies carried out in a village environment which showed strong pollution of the groundwater resources of the settlements [59][60][61][62].…”
Section: Water Quality Changes After the Construction Of The Sewerage Networksupporting
confidence: 92%
“…These results are consistent with the results of other studies carried out in a village environment which showed strong pollution of the groundwater resources of the settlements [59][60][61][62].…”
Section: Water Quality Changes After the Construction Of The Sewerage Networksupporting
confidence: 92%
“…Usage of different tools and techniques (e.g., numerical modelling, geographical information systems (GIS)) by both scientific communities and decision makers for groundwater quality assessment and management has rapidly increased over the past few decades [27][28][29][30]. A GIS is one of the proven vital tools in studies of groundwater for different purposes (spatial distribution of contaminants, estimating the effect of land-use/land-cover (LULC) changes on water quality, overlay analysis for estimating groundwater potential, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…GIS has been widely applied to groundwater contamination studies to determine potential zones of vulnerability to surficial contamination (Stark et al 1999;Davis et al 2002;Capri et al 2009; Sener and Davraz 2013; Jasrotia and Kumar 2014; Edet 2014; Tokatli 2014; Barroso et al 2015;Bozdag 2015), or to create interactive karst databases (see Gao and Zhou (2008) for a review of GIS applications to karst). Regarding the land use impact on groundwater quality, Khan et al (2011Khan et al ( , 2017 discuss two case studies of GIS application to calculate groundwater quality index and to prepare a map of groundwater sustainability in terms of water quality.…”
Section: Methodsmentioning
confidence: 99%